2020
DOI: 10.1093/brain/awaa021
|View full text |Cite
|
Sign up to set email alerts
|

Soluble TREM2 is elevated in Parkinson’s disease subgroups with increased CSF tau

Abstract: Parkinson’s disease is the second most common neurodegenerative disease after Alzheimer’s disease and affects 1% of the population above 60 years old. Although Parkinson’s disease commonly manifests with motor symptoms, a majority of patients with Parkinson’s disease subsequently develop cognitive impairment, which often progresses to dementia, a major cause of morbidity and disability. Parkinson’s disease is characterized by α-synuclein accumulation that frequently associates with amyloid-β and tau fibrils, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 59 publications
2
43
0
Order By: Relevance
“…sTREM2 sTREM2 is detected in human cerebrospinal fluid (CSF), and its levels are elevated in CSF of patients with various neurological conditions, such as MS, AD, Parkinson's disease (PD), frontotemporal dementia (FTD) associated with progranulin (GRN) mutations, natural aging in cognitively unimpaired individuals, and in the plasma of Down syndrome patients (Falcon et al, 2019;Heslegrave et al, 2016;Piccio et al, 2008Piccio et al, , 2016Suá rez-Calvet et al, 2016a, 2016bWeber et al, 2020;Woollacott et al, 2018). Matching CSF concentrations of sTREM2 with other measures of human brain function revealed that sTREM2 corresponds to a genetic AD risk status (Deming et al, 2019;Piccio et al, 2016;Suá rez-Calvet et al, 2016a and correlates with disease hallmarks: total tau and phospho-tau181P levels in CSF in AD patients and total tau in PD patients (Heslegrave et al, 2016;Wilson et al, 2020). These results suggested that sTREM2 levels reflect a change in microglia activation status in response to already established neuronal degeneration and that CSF sTREM2 concentration can be used as a surrogate immune biomarker of neuronal injury (Piccio et al, 2016;Suá rez-Calvet et al, 2016b.…”
Section: Diverse Trem2 Roles In Diseasementioning
confidence: 99%
“…sTREM2 sTREM2 is detected in human cerebrospinal fluid (CSF), and its levels are elevated in CSF of patients with various neurological conditions, such as MS, AD, Parkinson's disease (PD), frontotemporal dementia (FTD) associated with progranulin (GRN) mutations, natural aging in cognitively unimpaired individuals, and in the plasma of Down syndrome patients (Falcon et al, 2019;Heslegrave et al, 2016;Piccio et al, 2008Piccio et al, , 2016Suá rez-Calvet et al, 2016a, 2016bWeber et al, 2020;Woollacott et al, 2018). Matching CSF concentrations of sTREM2 with other measures of human brain function revealed that sTREM2 corresponds to a genetic AD risk status (Deming et al, 2019;Piccio et al, 2016;Suá rez-Calvet et al, 2016a and correlates with disease hallmarks: total tau and phospho-tau181P levels in CSF in AD patients and total tau in PD patients (Heslegrave et al, 2016;Wilson et al, 2020). These results suggested that sTREM2 levels reflect a change in microglia activation status in response to already established neuronal degeneration and that CSF sTREM2 concentration can be used as a surrogate immune biomarker of neuronal injury (Piccio et al, 2016;Suá rez-Calvet et al, 2016b.…”
Section: Diverse Trem2 Roles In Diseasementioning
confidence: 99%
“…Associations between CSF sTREM2, total tau (t‐tau), and phosphorylated tau 181 (p‐tau) indicate that increased sTREM2 denotes microglial responses to tauopathy and the first signs of neurodegeneration 24–26 . However, this response is not AD‐specific 27,28 . In AD, the CSF level of sTREM2 seems to change during the course of the disease, with several studies showing a peak in the early symptomatic stage of sporadic, 24,25,29 and dominantly inherited AD 25 .…”
Section: Introductionmentioning
confidence: 99%
“…(Falcon et al, 2019;Heslegrave et al, 2016;Suarez-Calvet et al, 2016;Suárez-Calvet et al, 2016. It was found that sTREM2 contributes to the inherited AD risk status after comparing sTREM2 CSF levels with other human brain function studies (Deming et al, 2019;Falcon et al, 2019) and corresponds to the AD characteristics: Phospho-tau181P and total CSF tau levels in patients with AD and total tau in patients with PD (Heslegrave et al, 2016;Wilson et al, 2020).…”
Section: Association Of Strem2 and Admentioning
confidence: 98%